تأثير نموذج التعليم التعاوني بنوع جيكساو في فهم النصوص العربية الطلاب في مدرسة الزمرية المتوسطة القرآنية الإسلامية الداخلية سيمالانجانج - Octaviani, Aulindri; Dewi, Yelfi; Husni, Arman; Anas, Al Baihaqi (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
Learning model is one of the methods used by teachers to improve learning activities, especially in learning Arabic. Based on the initial observations, the researchers saw that in learning activities student had difficulty understanding Arabic texts, students’ enthusiasm for learning was reduced, student were not active in learning and teachers still used tradisional learning models. Therefore, researchers are interested in trying to use a learning model that is suitable for use in this study. One of them is the Jigsaw tipe cooperative learning model. Jigsaw type of cooperative learning model is a learning model that requires active students, eager to learn in small groups. The purpose of this study is to determine whether there is an effect or not using the Jigsaw type cooperative learning model on students’ understanding of Arabic texts. In this study, the researcher used a true experimental design with the post test only control group design. While the tools to collect data used by researchers are observation, interviews and post test exams. This research data is a quantitative descriptive research. As for the population and samples in this study, all 7th grade students of SMPQ al-Zamriyah Islamic Boarding School Simalanggang. Which consists of 2 classes, namely class A and class B. The total number of students is 40 peoples. The results of this study show that data analysis using the t-table test at the level of 5% (0,05) t-count > t-table, which is 5,873 > 2,024. So, the conclusion in this study is that the Jigsaw type of cooperative learning model has an effect on understanding Arabic texts for 7th grade students at SMPQ al-Zamriyah Islamic Boarding School.